Project-based edutainment in introducing culture and tourism to early childhood - Poerwati, Christiani Endah Poerwati; Cahaya, I Made Elia; Subagia, Ni Komang Theda Febrina; Parwata, I Made Yoga (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
Children can learn about culture and tourism through meaningful playing activities. The learning model that accommodates both playing and learning activities is edutainment based on project-based learning. This study aimed to determine the effectiveness of project-based edutainment in introducing culture and tourism to early childhood. This research was a quasi-experiment, designed using a post-test only control group design. The population of the study was 5-6-year-old children in PAUD Desa Dalung, Kuta Utara District. The data collection technique was through observation and documentation. Data was gathered using observation sheets and the data analysis used one-way analysis of variance (ANOVA). The results of the analysis showed a significant impact on the introduction of culture and tourism in the experimental group after applying edutainment-based learning. Based on the data analysis, it was concluded that there was a significant difference in the ability to recognise culture and tourism in children who followed the edutainment-based learning compared to those who followed conventional learning. Activities involving simple projects designed in a fun way could enhance children's ability to recognise culture and tourism. The research results provided an effective learning design to improve early childhood's ability to recognise culture and tourism.